Academy color encoding system (ACES) in the era of digital cinematography: A review on the implementation in polis evo two - Tan Teck Zee; M Fazmi Hisham (Akademi Seni dan Teknologi Kreatif, 2021)
Since the inception of digital cinematography, systemic colour management has been introduced from REC709 to REC2020, but not one colour management system that could be used universally. Thus, Academy Color Encoding System (ACES) was created, and it has become pivotal since its inception to unify all colour space available in motion pictures. Polis Evo Two (2018) was the first Malaysian film to use ACES from principal photography to Digital Cinema Package (DCP). This article would take the reader through the process taken by the researcher/cinematographer. Using a practice-based approach, this article hopes to share how ACES was implemented and solve some of the complex color disparities within the viewing platform. In light, this would help local cinematographers embrace ACES as an end-to-end pipeline for colour management.